Kajian Kehadiran Inang Primer pada Pertumbuhan Semai Cendana - Albertus Husein Wawo (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2004)
Sandalwood  (Santalum album L.)  is known as a fancy plant. Since they have  high economic value, it often over exploited.  As a consequence, the population  dramatically decreased  in their habitats.  Some efforts  have been  done  to conserve  this plant  in order to prevent their extinction, i.e.  seedling multiplication.  As a  hemiparasitic plant,  sandalwoods  need other  plants for a host which grow  around.  Therefore, determining of the the primary host is a necessary aspect in multiplication  of  sandalwood seedling.  This study  used  three  species  plants  to serve sandalwood seedling   as  primary host  in pot cultures consist of local leucaena (Leucaena glauca), vilosa (Acacia villosa)   and calliandra  (Calliandra  calothyrsus).   The results  of this study indicated   that A. vilosa  is better for a primary  host  than  L. glauca and  C. calothyrsus as well. Number of  root connection  between  sandalwood seedlings   and their hosts  have a close correlationship   to  the leaf  number  and the  sandalwood seedling   dry weight, whereas no significant correlationshifp to their height.